11: PROGRAM PLANNING, PRIORITIZING, AND IMPROVEMENT: A SIMPLE HEURISTIC. (10th October 2017) - Felten, Peter; Little, Deandra; Ortquist‐Ahrens, Leslie; Reder, Michael
Abstract : As educational developers working with multiple constituencies and demands on our time, how can we efficiently and creatively improve our programming and prioritize our efforts? In this chapter, we offer a simple heuristic to prompt quick yet generative examination of our goals or programs in relationship to three key characteristics of effective educational development on three different institutional levels. We then describe uses and applications of the tool and reflective process, which allow developers to efficiently gain insight into their work and effectively frame priorities for planning and improvement.